2010
DOI: 10.5713/ajas.2011.10022
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Different Mycotoxin Adsorbents against Blood and Liver Pathological Changes Induced by Mold-contaminated Feed in Broilers

Abstract: An experiment was conducted to determine the effects of different mycotoxin adsorbents including esterified glucomannan (EGM), hydrated sodium calcium aluminosilicate (HSCAS) and compound mycotoxin adsorbent (CMA) on performance, blood parameters, and liver pathological changes in broilers fed mold-contaminated feed. Two hundred and forty 10-day-old broilers were randomly assigned to one of the five dietary treatments including: i) control diet; ii) mold-contaminated diet; iii) moldcontaminated diet+0.05% EGM;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
4
14
1
Order By: Relevance
“…Basmacoğlu et al (2005) have shown that the dietary EGM supplementation at the dose of 0.10 per cent succeeded in significantly increasing the proteinemia in broilers during aflatoxicosis. Wang et al (2006) and Che et al (2011) also reported such observations.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Basmacoğlu et al (2005) have shown that the dietary EGM supplementation at the dose of 0.10 per cent succeeded in significantly increasing the proteinemia in broilers during aflatoxicosis. Wang et al (2006) and Che et al (2011) also reported such observations.…”
Section: Resultssupporting
confidence: 58%
“…Banlunara (2005) indicated that activities of ALP was increased by AFB1, whereas, were decreased by EGM. Che et al(2011) reported improved ALP levels by the feeding of mycosorb (0.05g/kg) in aflatoxicated broiler chickens.…”
Section: Serum Glutamate Pyruvate Transaminasementioning
confidence: 99%
“…It is predicted that, when more aflatoxin molecules are adsorbed by feed additives in the gastrointestinal tract, there are less negative effects on the target organs and blood biochemistry. These findings are in agreement with other studies reporting significant improvements with addition of YG in moldcontaminated diets (Aravind et al, 2003;Girish & Devegowda, 2006;Che et al, 2011).…”
Section: Effects Of Yeast Glucomannan and Sodium Bentonite On The Toxsupporting
confidence: 93%
“…Zeolites (Modirsanei et al, 2004;Khadem et al, 2012), bentonites (Ibrahim et al, 2000;Rosa et al, 2001;Eraslan et al, 2004;Abousadi et al, 2007;Manafi, 2009;, and yeast and esterified glucomannans (Raju & Devegowda, 2000;Aravind et al, 2003;Girish & Devegowda, 2006;Che et al, 2011;Mosca & Marichal, 2011;Rosa et al, 2012) have been shown to reduce aflatoxin absorption in the gastrointestinal tract. Some studies suggest that the best approach for decontamination is biological degradation, using yeast and yeast components, which may remove aflatoxin under mild conditions, without having to use harmful chemicals or causing any noticeable losses in the nutritional value or palatability of diets (Shetty et al, 2007;Oguz, 2012).…”
Section: Effects Of Yeast Glucomannan and Sodium Bentonite On The Toxmentioning
confidence: 99%
See 1 more Smart Citation